Evidence of electron neutrino appearance in a muon neutrino beam - Abe, K; Abgrall, N; Aihara, H; Akiri, T; Albert, J; Andreopoulos, C; Aoki, S; Ariga, A; Ariga, T; Assylbekov, S; Autiero, D; Barbi, M; et al. (2013)
The T2K Collaboration reports evidence for electron neutrino appearance at the atmospheric mass splitting, |Δm322|≈2.4×10-3 eV2. An excess of electron neutrino interactions over background is observed from a muon neutrino beam with a peak energy of 0.6 GeV at the Super-Kamiokande (SK) detector 295 km from the beam's origin. Signal and background predictions are constrained by data from near detectors located 280 m from the neutrino production target. We observe 11 electron neutrino candidate events at the SK detector when a background of 3.3±0.4(syst) events is expected. The background-only hypothesis is rejected with a p value of 0.0009 (3.1σ), and a fit assuming νμ→νe oscillations with sinâ¡22θ23=1, δCP=0 and |Δm322|=2.4×10-3 eV2 yields sinâ¡22θ13=0.088-0.039+0. 049(stat+syst). © 2013 American Physical Society.